Experimental evaluation of the subchronic toxicity of Phong Te Thap Ba Giang - Van Anh, Pham Thi; Hung, Bui Tien; Hai, Vu Xuan; Ha, Nguyen Thi; Duong, Dau Thuy (Tạp chí Nghiên cứu Y học, 2025)
Musculoskeletal disorders have become a global health burden. Phong Te Thap Ba Giang is a traditional medicine that has been used for a long time to treat various musculoskeletal disorders. This study was conducted to evaluate the subchronic toxicity of Phong te thap Ba Giang in experimental animals. Phong te thap Ba Giang was administered orally to Wistar rats at 4.32 pills/kg/day (equivalent to the recommended clinical dose) and 12.96 pills/kg/day (three times higher than the dose equivalent to the recommended clinical dose) for 12 consecutive weeks. The results showed that Phong Te Thap Ba Giang at both doses did not affect the general condition, body weight, hematological and biochemical parameters, and histological images of the liver and kidneys compared with the control group and baseline. In conclusion, Phong te thap Ba Giang did not cause subchronic toxicity in Wistar rats.